Role of leadership on organizational learning in private universities of Bangladesh - Uddin, Md Mahi; Khan, Mohammad Aktaruzzaman; Ali, Kalsom (IIUC Studies, 2017)
The study investigates the influence of leadership styles, i.e. transactional and transformational on promoting organizational learning in some selected private universities in Chittagong, Bangladesh. The study used a quantitative research design. Data have been collected from three private universities of Chittagong through a survey instrument. The study analyzed in total 147 matched completed questionnaires. The findings of the study revealed that contingent reward of transactional leadership and idealized influence and individualized consideration of transformational leadership played significant and positive influence on enhancing organizational learning. Although, findings of this research did not report any significant impact of management by exception-active and management by exception-passive as constructs of transactional leadership as well as inspirational motivation and intellectual stimulation as dimensions of transformational leadership style on organizational learning. The study extends present literature in the field by relating leadership styles and organizational learning focusing on emerging economies particularly in the context of Bangladesh. IIUC Studies Vol.14(2) December 2017: 09-34